Failure mechanism and early warning of an excavation-induced soil landslide - Wu, Yingfeng; Xue, Demin; Chen, Kai; Dai, Cong; Hang, Zhenyuan; Wu, Zhongteng; Zhang, Shuai (Frontiers in Earth Science, 2024)
Due to the uncertainty in soil landslide failure mechanisms, lack of early warning systems for soil landslides and adoption of improper excavation configurations, soil landslides accidents triggered by highway excavation in Chinese mountainous areas generally require expensive remedial measures. This paper describes a soil landslide associated with excavation through integrating field reconnaissance and FEM simulation. According to the obtained results, the adoption of toe excavation and the presence of a silty clay layer are the two main factors contributing to the failure of the soil landslide, and a strong negative correction was observed between the toe excavation and surface displacement and the safety factor of the investigated cut slope; therefore, a four-level early warning system for this excavation-induced soil landslide was established by employing toe excavation and surface displacement thresholds as the warning indicators. Lastly, a preferable excavation configuration was proposed to facilitate excavation designs in similar landslide-prone areas.